Skeletal Muscle Type-Dependent Effect of Atorvastatin on FoxO3a and Akt in Hypercholesterolemic Rats - Anna Gawędzka; Jagoda Drąg; Małgorzata Knapik-Czajka; Małgorzata Belczyk; Angelika Szafran; Iga Szlachta (Polskie Towarzystwo Farmaceutyczne, 2023)
Statins are one of the most commonly used lipid-lowering drugs reducing the risk of mortality due to cardiovascular diseases. They are well tolerated and have relatively few side effects which mainly affect skeletal muscle. The impact of statins on skeletal muscle functions depends on the composition of the muscle fibers type. One of the mechanisms of statin-induced myopathy is imbalance between muscle protein synthesis and breakdown.Transcription factor FoxO3a is a key factor regulating muscle protein breakdown. The activity of FoxO3a is regulated namely by phosphorylation via PI3K/Akt pathway. Active, phosphorylated Akt catalyzes the phosphorylation and thus inactivation of FoxO3a. The purpose of our study was to evaluate the effect of atorvastatin on FoxO3a and Akt in different skeletal muscles in rats with diet-induced hypercholesterolemia. Atorvastatin (20 mg/kg b.w./day) or the vehicle was administered orally 21 days. FoxO3a, Akt and their phosphorylated protein levels were assayed by Western blot in gastrocnemius and soleus muscle. Additionally, muscle total protein level and serum CK activity were measured. In the gastrocnemius muscle atorvastatin decreased total FoxO3a and P-FoxO3a levels with no changes in Akt and P-Akt level. In contrast, in soleus muscle atorvastatin did not change the level of P-FoxO3a. However, total FoxO3a and the P-Akt level decreased. Serum CK activity did not change in both muscle under atorvastatin treatment. In conclusion, the results of our study indicate that atorvastatin affects FoxO3a and Akt in a muscle type-dependent manner.